Hubungan Work Life Balance dengan Kepuasan Kerja pada Anggota Polisi Polres Karanganyar - Qanita Alifatul Azzahra; Sri Ernawati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Work life balance is an individual’s ability to carry out work with good commitment and be responsible for activities outside of work, which also involves a balance between work and family. Job satisfaction is a series of feelings that employees experience towards their work, whether it is pleasant or unpleasant. This research aims to determine the relationship between work life balance and job satisfaction among police officers at Karangnyar Police. The research method used in this research is a quantitative method. The population in this study were members of the Karanganyar Police, while the sample in this study was members of the Samapta police unit (Sat Samapta) totaling 52 respondents. The results of hypothesis testing show that the hypothesis proposed in this research cannot be accepted, namely because there is no significant or significant relationship between Work Life Balance and Job Satisfaction. The results of the correlation analysis between Work Life Balance and Job Satisfaction are 0.042 with a significance level of p = 0.768 (p > 0.05).